(untitled) (Journal of the College of Basic Education, 2022)
Hassan Al-Suhail Sheikh Bani Tamim, who had an important role in the transition of the Bani Tamim tribe in Aqraqof from Bedouinism to the stage of settlement and agriculture.He was one of the strongest supporters during the British occupation of British policy, and that a national government could not be formed without British guidance, and from this standpoint he refused to participate in the 1920 revolution, and after King Faisal was crowned on the throne he was more loyal to the monarchy, as he worked against the movement of Mays 1941, which led to to his arrest.And he played an important role in the politics of Iraq, as he represented the Baghdad Brigade for four electoral cycles, in addition to his participation in political parties, and he had positions on internal and external political issues such as the issue of Palestine, and after 1955 he left political work until his death in 1957.